Musical training in Tribal West Africa - Smith, Edna M. (International Library of African Music, 1962)
With the possible exception of the "Bush Schools" set up by the tribes for initiation purposes or by the secret societies such as the Leopard Society, traditional instruction in Tribal West Africa was not on an institutional basis. It was based on the principle of slow absorption of musical experience and active participation rather than formal teaching. The social organization was helpful, for the child was absorbed into all activities of the tribe and these activities were generally connected with music. The child's first lessons in music were given by his mother. Immediately after birth the child was placed on his mother's back while she went about her daily tasks. In this way the child from his birth was introduced to the music of his culture. He learned what the music required in terms of both bodily movement and vocal effort. He formed through these early experiences the habit of listening to the music of his people.
Keywords: Music; Ashanti (African people); Ethnomusicology; Folklore; Education; African Music; Ghana; Social Life; Social Customs